CircHUWE1 Exerts an Oncogenic Role in Inducing DDP-Resistant NSCLC Progression Depending on the Regulation of miR-34a-5p/TNFAIP8. (3rd December 2021) - Yang, Xueliang; Sun, Quan; Song, Yongming; Li, Wenli
Abstract : Background . Circular RNAs (circRNAs) are reported as competing endogenous RNAs (ceRNAs) and play key roles in non-small-cell lung cancer (NSCLC) progression. Thus, this study was aimed at clarifying underlying molecular mechanisms of circHUWE1 in NSCLC. Methods . The quantitative real-time polymerase chain reaction (RT-qPCR) and western blot analyses were used for examining circHUWE1, microRNA-34a-5p (miR-34a-5p), and tumor necrosis factor alpha-induced protein 8 (TNFAIP8). IC50 of cisplatin (DDP) in A549/DDP and H1299/DDP cells and cell viability were analyzed by the Cell Counting Kit 8 (CCK-8) assay. Colony forming assay was performed to assess colony forming ability. Cell apoptosis and cell cycle distribution were determined by flow cytometry. Migrated and invaded cell numbers were examined by transwell assay. The association among circHUWE1, miR-34a-5p, and TNFAIP8 was analyzed by dual-luciferase reporter and RNA immunoprecipitation assays. A xenograft experiment was applied to clarify the functional role of circHUWE1 in vivo . Results . circHUWE1 was upregulated in NSCLC tissues and cells, especially in DDP-resistant groups. circHUWE1 downregulation inhibited DDP resistance, proliferation, migration, and invasion while it induced apoptosis and cell cycle arrest of DDP-resistant NSCLC cells, which was overturned by silencing of miR-34a-5p. TNFAIP8 was a functional gene of miR-34a-5p, and the suppressive effects of miR-34a-5p overexpression on DDP-resistant NSCLC progression were dependent on the suppression of TNFAIP8. circHUWE1 inhibition also delayed tumor growth of DDP-resistant NSCLC cells. Conclusion . circHUWE1 functioned as a promoter in DDP-resistant NSCLC by interaction with miR-34a-5p-TNFAIP8 networks, providing novel insight into DDP-resistant NSCLC diagnosis and treatment.